The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36416/1806-3756/e20220235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, outcomes, and predictors of multidrug-resistant nosocomial lower respiratory tract infections among patients in an ICU

Abstract: Objective: To determine the prevalence, outcomes, and predictors of multidrug-resistant nosocomial lower respiratory tract infections (LRTI) in patients in an ICU. Methods: This was an observational cohort study involving patients with nosocomial LRTI (health care-associated pneumonia, hospital-acquired pneumonia, or ventilator-associated pneumonia). Data were prospectively collected between 2015 and 2019. The multidrug-resistant pathogens (MDRPs) identified in the isolates studied included resistant to extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Numerous retrospective studies in several countries have shown that the occurrence of infections caused by MDRO in patients admitted to the intensive care unit (ICU) is a signi cant concern [3], and will greatly affect the treatment effect of the disease. MDRO infection in the ICU is associated with increased inpatient mortality, readmission rates, medical costs, and length of stay [4][5][6]. According to a retrospective study of carbapenem-resistant Gramnegative bacilli (CR-GNB) infections in Malaysia, pneumonia (40.7%) and bacteremia (25.5%) were the most common, and the overall hospital mortality rate was high (41.4%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous retrospective studies in several countries have shown that the occurrence of infections caused by MDRO in patients admitted to the intensive care unit (ICU) is a signi cant concern [3], and will greatly affect the treatment effect of the disease. MDRO infection in the ICU is associated with increased inpatient mortality, readmission rates, medical costs, and length of stay [4][5][6]. According to a retrospective study of carbapenem-resistant Gramnegative bacilli (CR-GNB) infections in Malaysia, pneumonia (40.7%) and bacteremia (25.5%) were the most common, and the overall hospital mortality rate was high (41.4%) [7].…”
Section: Introductionmentioning
confidence: 99%